30:70 : architecture as a balancing act - Choban, Sergeĭ, 1962-; Sedov, Vl. V. (Vladimir Valentinovich); Schulz, Bernhard, 1953- (Berlin : DOM Publishers, 2018)
"Never before have so many buildings been constructed as today, and never has architecture had so many technological and design possibilities at its disposal. And yet there is a sense of unease about contemporary architecture. In their book, Sergei Tchoban and Vladimir Sedov show how in modern times we have lost the balance between outstanding works of architecture and the background structures that surround them, with every building striving to assert itself in relation to all the others - to drown them out if it can. Yet the modern age is certainly capable of developing a harmony of contrasts - it has everything it needs at its disposal. After taking the reader on a foray through 2,500 years of architectural history, the authors arrive at the anomaly of modernism. They show what contemporary architecture must take into account if it is to achieve a satisfactory overall architectural impression that is harmonious in an entirely new way"--Back cover.
Translation of: 30:70 : arkhitektura kak balans sil.
Includes index.
Keywords: Architecture -- History; Architecture